Prospek Dan Tantangan Hukum Internasional Di ASEAN Dan Indonesia Pasca Piagam ASEAN Dari Sisi Perjanjian Internasional - Eddy Pratomo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
After the establishment of Asian Charter, the agenda to which Asian countries shall address is that its implementation urgently requires a strong political will and the sufficient supporting framework. For Indonesia, the prospect and challenge for the implementation of this charter is mostly in the form of the reformation of the law pertinent to the law of international organization. From international perspective, the position of Indonesia as the hosts of the Asian headquarter may significantly affect the development of international law, especially on he law of international organization.